Bektashi Lodges and Zawiyas in Didymoteicho in the Ottoman Sources from the XVth and XVIth Centuries - Kayapınar, Levent (Journal of Alevism-Bektashism Studies, 2018)
The Ottomans went on to the Balkans after taking the Çimpe castle in 1352 and the castle of Gelibolu in 1354, and there they continued their conquests. In a short time, many cities in Thrace were came under the Ottoman rule. One of the first conquered cities in Thrace was the city of Dimetoka, today located within the borders of Greece. Dimetoka, included in the Ottoman administrative division and located in the region of Seydi Ali Sultan’s zawiya, was turned into a district (kaza) centre affiliated to Çirmen Sanjak. After being taken under the control of the Ottoman Empire, in Dimetoka and in its regions the Ottoman raider lords (uç bey) and religious leaders began to establish their lodges and zawiyas. These are followed by the establishment of foundations. Among those who founded these institutions and settlements, we come across raider lords such as Turhan Bey, Malkoç Bey and Mezid Bey. As for the religious leaders, we can mention Abdal Cüneyd, Çakmak Dede, Ahi Dinek, Kanad Abdal and Hızır Baba. The zawiyas and foundations established by the raider lords and religious leaders were legitimated due to the berats given by the Ottoman sultans such as Murad I, Yıldırım Bayezid, Mehmed I, Murad II and Mehmed the Conqueror. Among the income sources of these zawiyas and foundations, we found the villages named as Sultan Shah, Göç Beyi, Bektash and Ziyaret Beylü. In addition, the presence of Bektashane in some lodges reveals the relationship of the early religious leaders in the Dimetoka region with Bektashism. The Ottoman registry books contain important and rare information about foundations, dervish lodges and zawiyas established in the region. These registers belong to the period between 1485 and 1574. In this study, the zawiyas and lodges, established in the Dimetoka region, and some of the villages, which are among their sources of income, were analysed by using the registry books.
Keywords: Bektashi; Ottoman; Rumelia; Thrace; Lodges; Zawiyas